Methacrylate Functionalized MWCNTs/PDMS-Polyurethane Methacrylate UV-Curable Nanocomposites - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN (SPRINGER, 2018)
Polyurethane (PU)-carbon nanotube composites have gained interest in the area of aerospace, automobiles, fuel cells electrical appliances and communication related applications. However, there is still insufficient information on PU-carbon nanotube composites. In this study, hydrophobic and high performance UV-curable nanocomposites were prepared by using surface functionalized multi-walled carbon nanotubes (MWCNT). First, MWCNT were treated with acid solution (HNO3/H2SO4) and then grafted with poly(ethylene glycol) methacrylate (PEGMA) to introduce UV-photopolymerization sites. Different amounts of methacrylate tethered MWCNT and sol-gel precursor or hydrophobic nanosilica were added to PDMS-polyurethane methacrylate based UV-curable formulation and cured by UV irradiation. The composites were also thermally treated (post-cure). The effects of the carbon nanotube, the sol-gel precursor and the hydrophobic nanosilica content on thermal, mechanical and morphological properties of the nanocomposite films were investigated. The addition of the sol-gel precursor and hydrophobic nanosilica increased thermal stability with regard to the base formulation. The addition of MWCNT and silica increased the modulus of the composite from 245 to 318 MPa with regard to the base formulation. Moreover, the thermal decomposition range was increased with addition of the modified MWCNTs. The morphology of the composite films was also carried out by using scanning electron microscopy (SEM). Morphological investigations showed that better dispersion of nanoparticles and performance were achieved when the surface functionalized MWCNTs and hydrophobic silica nanoparticles used together in nanocomposite preparation.
Keywords: Carbon nanotube; Surface functionalization; UV curing; Nanocomposite; MULTIWALLED CARBON NANOTUBES; SURFACE MODIFICATION; POLYMER COMPOSITES